A Review of Smart Parking System based on Internet of Things. - Kaur, Harkiran; Malhotra, Jyoteesh (International Journal of Intelligent Systems and Applications in Engineering, 2018)
: The Internet of Things expands the wireless paradigm to the edge of the network, which enables to develop a different kind of applications or services. By using IoT the application becomes more reliable, flexible or portable. It has a large amount of nodes on the various geographic positions, to increase the awareness of location or reduce the latency. There are numerous IoT applications like smart grid, smart hospital, smart industry, smart traffic management etc. In this paper, we describe the smart traffic management and parking system using the internet to control the chaos and also discuss the various researches on this concept.